Interactive Multimedia CD Design Chemistry Lesson In Concept Training Material and amendment For Class X Vocational High School (SMK) - Wijaya, Indra; Sefriani, Rini (-)
This research aims to create  Multimedia Interactive CD that helps for students in the learning process, especially in learning Chemistry. This research was conducted in subjects with material chemistry concept of matter and its changes. This research is R & D (research and development). Multimedia  interkatif CD later will be tested to the students of class X Vocational High School .Instrumen used in collecting data in the form questionnaire, with Likert scale with respondents Vocational High School students from several schools. The data were analyzed using Microsoft Excel 2007. Based on the research that has been done, the obtained to display multimedia interactive CD rhitung value = 0.49 and compared with r kritis, = 0.3 the display of multimedia interactive CD declared valid, and for ease of navigation CD Multimedia interactive rhitung value = 0.48 and compared with rkritis, = 0.3  the ease of navigation interactive multimedia CD declared valid, and for aspects of Multimedia rhitung value = 0.58 and compared with rkritis, = 0.3 and Multimedia aspects declared valid,for the media  learning the value of rhitung = 0.50 and compared with rkritis, = 0.3 and the media to learn declared valid, thus Multimedia interktif CD Chemistry is feasible to be used as an additional medium / aids in teaching Chemistry for class X Vocational High School.